Grundvorstellungen Funktionalen Denkens handlungsorientiert ausschärfen – Eine Interviewstudie zum Umgang von Schülerinnen und Schülern mit haptischen Modellen von Funktionsgraphen (mathematica didactica, 2021)
The development of functional thinking (Vollrath, 1989) is a decisive element of precalculus courses. This article is intended to show how basic concepts about covariation and the function as a whole can be developed by using tactile models of graphs of functions in mathematics class. In an empirical study, the conceptual development of six students of a tenth grade was investigated in a controlled environment. The video recordings of the working phases and of subsequent expert interviews were categorized using the method of qualitative content analysis according to Mayring (2010). The theoretical background is the theory of basic concepts according to vom Hofe (1992) and the theory of subjective domains of experience according to Bauersfeld (1983) embedded in the concept of empirical theories according to Burscheid and Struve (2010).